Eu-wide carbon pricing: Macroeconomic effects and distributional implications - Claudia Kettner; Daniela Kletzan-Slamanig; Mark Sommer; Gerhard Streicher (Austrian Institute of Economic Research (WIFO), 2024)
While the EU-wide carbon price has already been adopted for the buildings and transport sectors with ETSê2, detailed analyses of the macroeconomic and distributional effects (both within and between countries) are scarce. We use the macroeconomic model ADAGIO to estimate the effects of EU-wide carbon pricing. For two case study countries (Austria and Poland), which differ considerably in terms of the structure of their energy systems and economies, results are discussed along with the EU 27. We focus on the macroeconomic and GHG effects of the introduction of a carbon price under various revenue recycling options. Moreover, the distributional effects of the policy scenarios are investigated. The introduction of carbon pricing leads to negative macroeconomic effects for the EU 27, which vary in level depending on the recycling option as well as the assumed model closure and exchange rates. For Austria and Poland, slightly positive macroeconomic effects are found in some simulations. Additionally, our analysis confirms the efficiency-equity trade-off in the context of carbon pricing with respect to different revenue recycling options.
Keywords: Q54; Q58; H23; C67; D57; 330; carbon pricing; revenue recycling; macroeconomic effects; distributional impacts; multi-regional Input-Output modelling